Hemimegalencephaly and intractable focal seizures related to NPRL3 mutation with variable familial expressivity treated with anatomic hemispherectomy - Richard B. Carozza; Robert P. Naftel; Asha Sarma; Emma G. Carter (Wiley, 2023)
Abstract Introduction Hemimegalencephaly is a syndrome of dysplastic cortical formation, with hamartomatous overgrowth of a cerebral hemisphere, classically associated with intractable focal epilepsy, hemiparesis, and hemianopia. While often cryptogenic, associations with various proliferative syndromes have been implicated, such as in our patients. Patient Description We present a newborn with intractable focal epilepsy due to hemimegalencephaly caused by an inherited mutation in nitrogen permease regulator‐like 3 (NPRL3). He underwent anatomic hemispherectomy. His phenotype was more severe than that of other family member, which is consistent with recent studies suggesting that NPRL3 and other genes implicated in familial focal epilepsy with variable foci (FFEVF) produce a phenotypic range. Conclusions Hemimegalencephaly can produce intractable focal epilepsy and has been associated with various genetic causes, including NPRL3 mutations. We describe the fifth patient with hemimegalencephaly secondary to NPRL3 and the only one to undergo anatomic hemispherectomy. Given the small number of documented patients, more research is needed to elucidate the role of interventions such as sirolimus and palliative surgical procedures such as hemispherectomy.